Experienced Mathematics Teachers PCK in the Use of Learner-Centred Approaches in Tanzania ’ s Secondary Schools - Anney, Vincent Naano; Bulayi; Makungu (Papers in Education and Development, 2020)
The study assessed experienced Mathematics teachers ' pedagogical content knowledge (PCK) in the use of learner-centred approaches (LCA) and did not focus on a specific topic when teaching the subject. The study was guided by the multiple case study design underpinned by an interpretive research paradigm to assess four experienced Mathematics teachers ' PCK in the use of LCA. Purposive sampling was applied to identify experienced teachers based on the premise PCK expands with the teachers ' training and experience. The four experienced Mathematics teachers had at least five years of teaching experiences and their school and government authorities treated them as experts in teaching Mathematics. Consequently, two experienced teachers were selected from the categories of high performing schools and two others from the low performing schools in two political administrative districts. Data were collected through classroom observations, interviews, teachers ' self-reflection, and documentary review. Data were analysed thematically using three out of five components of the teachers ' PCK as identified by Magnusson, Krajacik, and Borko (1999) which served as the conceptual framework of the study. The results indicate that experienced Mathematics teachers demonstrated little knowledge of the LCA when teaching Mathematics concepts. Little knowledge of LCA led to their difficulties in put learners at the centre of their lessons. In fact, the experienced Mathematics teachers ' classroom practices were mostly orientated towards teacher-centred approaches and were largely ineffective in transforming the components of PCK in the use of LCA and had little knowledge of learner-centred instructional strategies. The study concluded that although the teachers 95 were trained and experienced, they had underdeveloped component of PCK in the use of LCA. Therefore, the study recommends that LCA be integral part of in-service teachers ' training programmes in secondary schools to support those mathematics teachers who have not received training in LCA.